2019
DOI: 10.1186/s10020-019-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis elucidates unique influences on purine / pyrimidine metabolism by xanthine oxidoreductase inhibitors in a rat model of renal ischemia-reperfusion injury

Abstract: Background Clinically applied as anti-gout drugs, xanthine oxidoreductase (XOR) inhibitors, especially the potent, selective, non-purine-analog XOR inhibitors febuxostat and topiroxostat, exert organ-protective effects. We tested the hypothesis that preservation of tissue concentrations of high-energy phosphates, such as ATP and ADP, contributes to organ-protective effects through CE-TOFMS metabolomics. Methods Rats were subjected to 30 min of renal ischemia-reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…On the other hand, hypoxanthine could aggravate myocardial and renal graft ischemia/reperfusion injury by ROS (36,37). It is considered that xanthine oxidoreductase (XOR) leads to reduced uracil and hypoxanthine and increased uric acid in our study (38,39).…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, hypoxanthine could aggravate myocardial and renal graft ischemia/reperfusion injury by ROS (36,37). It is considered that xanthine oxidoreductase (XOR) leads to reduced uracil and hypoxanthine and increased uric acid in our study (38,39).…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, there are also studies in which its oral administration prior to ischemia instauration does demonstrate an antioxidant effect, as evidenced by a reduction in HID and a decrease in the production of oxidative stress markers such as malondialdehyde (MDA) [33]. Other studies performed in a renal IRI mode have shown the beneficial effect of XO inhibition [34][35][36][37][38]. After prophylactic administration of allopurinol, a decrease of up to 75% in the damage was noticed, both biochemical and anatomopathological.…”
Section: Discussionmentioning
confidence: 99%
“…The purine salvage pathway plays an important role in ATP maintenance, as evidenced by the low levels of ATP in Lesch-Nyhan syndrome patients who have a mutation of hypoxanthine-guanine phosphoribosyltransferase (HGPRT), a crucial enzyme in the salvage pathway 22 . XOR inhibition results in the accumulation of hypoxanthine, which in turn leads to the activation of salvage pathway via HGPRT 23,24 . Given these previous reports, the restoration of iATP by febuxostat is mainly due to the activation of salvage pathway because febuxostat increased not only ATP but also GTP (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%